Nocardiosis in freshwater reared Chinook salmon (Oncorhynchus tshawytscha). Issue 4 (4th July 2017) - Brosnahan, CL; Humphrey, S; Knowles, G; Ha, HJ; Pande, A; Jones, JB
Abstract: CASE HISTORY: An investigation was conducted to identify the cause of mortalities in freshwater reared Chinook salmon ( Oncorhynchus tshawytscha ). Mortalities occurred in juvenile salmon, at a salmon rearing facility in the South Island of New Zealand. The affected fish were from a pen inside the facility with no surrounding pens or other year classes affected. CLINICAL FINDINGS: Clinically affected fish presented with skin lesions. The majority of skin lesions were unruptured, boil-like, raised circular masses up to 4 cm in diameter, particularly on the dorsolateral aspects and the flank. A number of fish presented with large ulcers resulting from rupturing of the raised lesions described above. This clinical presentation showed similarities to that of furunculosis caused by typical Aeromonas salmonicida, a bacterium exotic to New Zealand. LABORATORY FINDINGS: Samples were taken from two representative fish in the field for histopathology, bacterial culture and molecular testing. Histopathological findings included granulomatous lesions in the kidney, liver, spleen and muscle. When stained with Fite-Faraco modified acid fast stain filamentous branching rods were identified within these granulomas. Following bacterial culture of kidney swabs pure growth of small white matt adherent colonies was observed. This isolate was identified as a Nocardia species by biochemical testing and nucleotide sequencing of the partial 16S rRNA gene. All samples were negative for A. salmonicida based on bacterial culture and PCR testing. DIAGNOSIS: Nocardiosis caused by a Nocardia species. CLINICAL RELEVANCE: Nocardiosis in these fish was caused by a previously undescribed Nocardia species that differs from the species known to be pathogenic to fish: N. asteroides, N. salmonicida and N. seriole . This bacterium is likely to be a new or unnamed environmental species of Nocardia that has the potential to cause disease in Chinook salmon under certain conditions. The clinical presentation of this Nocardia species manifested as raised, boil-like skin lesions which has similarities to the presentation of furunculosis caused by the bacterium typical A. salmonicida, a species exotic to New Zealand.